Skeletal muscle bioenergetics during all-out exercise: mechanistic insight into the oxygen uptake slow component and neuromuscular fatigue - Broxterman, Ryan M; Layec, Gwenael; Hureau, Thomas J; Amann, Markus; Richardson, Russell S (Journal of applied physiology (1985), 2017)
Although all-out exercise protocols are commonly used, the physiological mechanisms underlying all-out exercise performance are still unclear, and an in-depth assessment of skeletal muscle bioenergetics is lacking. Therefore, phosphorus magnetic resonance spectroscopy ( P-MRS) was utilized to assess skeletal muscle bioenergetics during a 5-min all-out intermittent isometric knee-extensor protocol in eight healthy men. Metabolic perturbation, adenosine triphosphate (ATP) synthesis rates, ATP cost of contraction, and mitochondrial capacity were determined from intramuscular concentrations of phosphocreatine (PCr), inorganic phosphate (P ), diprotonated phosphate ([Formula: see text]), and pH. Peripheral fatigue was determined by exercise-induced alterations in potentiated quadriceps twitch force (Q ) evoked by supramaximal electrical femoral nerve stimulation. The oxidative ATP synthesis rate (ATP ) attained and then maintained peak values throughout the protocol, despite an ~63% decrease in quadriceps maximal force production. ThusATP normalized to force production (ATP gain) significantly increased throughout the exercise (1st min: 0.02 ± 0.01, 5th min: 0.04 ± 0.01 mM·min ·N ), as did the ATP cost of contraction (1st min: 0.048 ± 0.019, 5th min: 0.052 ± 0.015 mM·min ·N ). Additionally, the pre- to postexercise change in Q (-52 ± 26%) was significantly correlated with the exercise-induced change in intramuscular pH ( = 0.75) and [Formula: see text] concentration ( = 0.77). In conclusion, the all-out exercise protocol utilized in the present study elicited a "slow component-like" increase in intramuscular ATP gain as well as a progressive increase in the phosphate cost of contraction. Furthermore, the development of peripheral fatigue was closely related to the perturbation of specific fatigue-inducing intramuscular factors (i.e., pH and [Formula: see text] concentration). The physiological mechanisms and skeletal muscle bioenergetics underlying all-out exercise performance are unclear. This study revealed an increase in oxidative ATP synthesis rate gain and the ATP cost of contraction during all-out exercise. Furthermore, peripheral fatigue was related to the perturbation in pH and deprotonated phosphate ion. These findings support the concept that the oxygen uptake slow component arises from within active skeletal muscle and that skeletal muscle force generating capacity is linked to the intramuscular metabolic milieu.